Primary Clinical Evaluation of Photodynamic Therapy With Oral Leukoplakia in Chinese Patients - Han, Ying; Xu, Si; Jin, Jianqiu; Wang, Xing; Liu, Xiaodan; Hua, Hong; Wang, Xiaoyang; Liu, Hongwei (Frontiers in Physiology, 2019)
Background: Photodynamic therapy (PDT) has demonstrated promising results in the treatment of oral leukoplakia. This study evaluated the clinical efficacy and side effects of photodynamic therapy in the treatment of Chinese patients with oral leukoplakia. Methods: Twenty-nine patients with oral leukoplakia were enrolled in this study, including patients with both homogenous and non-homogenous lesions and various dysplastic tissues. All patients received PDT using a 632 nm laser at 500 mW/cm2 power density at a dosage of 90-180 J/cm2 and with aminolevulinic acid (ALA) used as a photosensitizer. A fixing and restricting complex as well as high laser power density for PDT in oral cavity was applied. Results: An overall response rate of 86.2% was achieved in this study, including 55.2% complete remission and 31.0% partial remission. The only adverse events observed in subjects were transient local ulcer and pain. It is observed the PDT utilizing ALA showed strong effectiveness in patients with moderate to severe dysplasia, as less treatment time per cm2 of lesion is required. Conclusions: Topic ALA-PDT is effective to treat oral leukoplakia, especially for that with the presence of dysplasia. A fixing and restricting complex as well as high laser power density for PDT in oral cavity should be considered as an optimal choice.